2001
DOI: 10.1177/00912700122010276
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Variant Increase in Methylprednisolone Clearance in Patients with Acute Respiratory Distress Syndrome: A Population Pharmacokinetic Study

Abstract: Methylprednisolone (MP) disposition was evaluated in 20 individuals who participated in an ongoing randomized, double-blind, placebo-controlled study designed to evaluate the efficacy of MP in the treatment of acute respiratory distress syndrome (ARDS). MP (1 mg/kg) was given as a loading infusion over 30 minutes followed by a 1 mg/kg/day continuous i.v. infusion. Patients were switched to oral MP upon restoration of oral intake. MP plasma concentrations (n = 110) were determined using a specific HPLC method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
(37 reference statements)
0
19
0
1
Order By: Relevance
“…While the above simulations are based on average pharmacokinetic parameters in healthy individuals, GC elimination may be impaired in ARDS patients due to the well-described downregulation of drug metabolizing enzymes in generalized acute inflammation [ 33 ]. Yates et al reported that ARDS patients had an on average ~ 50% reduced clearance for methylprednisolone compared to normal values at therapy onset, which returned to normal values with reduction of systemic inflammation within a few days [ 34 ]. Correspondingly, methylprednisolone plasma concentrations were elevated relative to healthy individuals in the early treatment phase (Fig.…”
Section: Pharmacological Principles Of Glucocorticoid Actionsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the above simulations are based on average pharmacokinetic parameters in healthy individuals, GC elimination may be impaired in ARDS patients due to the well-described downregulation of drug metabolizing enzymes in generalized acute inflammation [ 33 ]. Yates et al reported that ARDS patients had an on average ~ 50% reduced clearance for methylprednisolone compared to normal values at therapy onset, which returned to normal values with reduction of systemic inflammation within a few days [ 34 ]. Correspondingly, methylprednisolone plasma concentrations were elevated relative to healthy individuals in the early treatment phase (Fig.…”
Section: Pharmacological Principles Of Glucocorticoid Actionsmentioning
confidence: 99%
“…It took about 2 days (41.1 h) of methylprednisolone therapy to achieve 50% of the improvement in clearance towards the re-establishment of homeostasis. [ 34 ]. b Methylprednisolone plasma concentration–time profile in ARDS patients receiving the aforementioned dosing regimen.…”
Section: Pharmacological Principles Of Glucocorticoid Actionsmentioning
confidence: 99%
“…[3032] Animal studies have shown that in acute lung injury, prolonged corticosteroids were shown to be effective in reducing edema and collagen deposition in lung, while premature withdrawal rapidly negated these positive effects. [3334] This seems a plausible explanation for the negative results observed in these studies with short course of high-dose MP.…”
Section: Corticosteroids For Prevention Of Ardsmentioning
confidence: 99%
“…P‐Glycoprotein as a determinant of intracellular cortisol accumulation. Our laboratory characterized methylprednisolone disposition in ARDS patients in an attempt to gain insight into the mechanism(s) of GC resistance 119. Interestingly, we found that the one individual who failed to respond to methylprednisolone therapy actually experienced deteriorating clearance over the course of therapy.…”
Section: Iii: Factors Affecting Cellular Response To Glucocorticoidsmentioning
confidence: 99%